Statistical characterization of vertical meteorological profiles obtained with the WRF-ARW model on the central Andes of Peru and its relationship with the occurrence of precipitation on the region - Moya-Álvarez, A.S. (2020)
The work carried out a characterization of tropospheric vertical profiles in rainy and dry seasons by behavior of thermodynamic indices obtained with the WRF model for the period January 2018–March 2019 on the central Andes of Peru and its relationship with rainfall in the region. A case study was also analyzed using sounding observation data. The precipitation observed were taken from 8 meteorological stations located in the Mantaro basin belonging to the National Meteorological Service of Peru. As a results, it was found that the behavior of the thermodynamic parameters responds to the general characteristics of each period. The level of condensation was always higher in the dry period, in which the lower troposphere was also more stable. The KI, TT, Sweat and CAPE indices were always higher in the rainy season, as was water vapor mixing ratio. The vertical shear was mostly higher in the dry period. The parameters that were most informative to precipitation forecasting in rainy period were the precipitation predicted by the model WRF, the average relative humidity of the 600–400 hPa layer and the water vapor mixing ratio in the layer itself. The shear in the 650–500 hPa and 550–400 hPa layer was also informative for two locations. In general, the indices were not very informative for the forecast of extreme rains. For the dry season, the relationship between thermodynamic indices and rainfall was not analyzed because it is very scarce at this time of year. The case study showed that in general, the thermodynamic parameters analyzed for each day, responded to the fact of a rainy day in relation to another dry day. © 2020 Elsevier B.V.